Effect of the Ethanol Extract of Red Okra Pods (Abelmoschus esculentus (L.) Moench) to Inhibit Cervical Cancer Cells Growth through Cell Cycle-Associated Oncogenes - Nabilatun Nisa; Sri Puji Astuti Wahyuningsih; Win Darmanto; Putut Rakhmad Purnama; Firli Rahmah Primula Dewi; Tipuk Soegiarti; Deya Karsari (Scientifica)
This study aims to evaluate the potency of ethanol extract of red okra pods (EEROP) in inhibiting growth of cervical cancer cells through repression of the cell cycle-associated oncogenes. The EEROP treatment was given to HeLa cells cultured with RPMI medium and incubated at 37°C with 5% CO2. The MTT method was used to measure HeLa cell growth and IC50 values. The mRNA levels of the three cell cycle-associated oncogenes (MYC, TYMS, and MDM2) were evaluated by qRT-PCR to determine the effect of EEROP treatment on the cell cycle. The lowest percentage of viable cells at 24, 48, and 72 hours after EEROP treatment was in the dose of 1000 μg/mL with a growth percentage of 71.60% at 24 hours, 55.61% at 48 hours, and 46.97% at 72 hours. The IC50 values were 2845, 1153, and 776.8 μg/mL for 24, 48, and 72 hours, respectively. The three oncogenes at a dose of 1000 μg/mL significantly decreased the lowest mRNA levels compared to other doses with MYC oncogene that experienced the greatest decrease. The mRNA level of dose 1000 μg/mL EEROP at the MYC oncogene was 0.014-fold changes, at the TYMS oncogene was 0.097-fold changes, and at the MDM2 oncogene was 0.028-fold changes. The EEROP has been shown to decrease the expression of three cell cycle-associated oncogenes. This is also supported by the growth of HeLa cells that did not increase throughout 24, 48, and 72 hours. However, further research is needed on the main active components in red okra that function as anticancer, so that in the future, okra can not only stop cancer cell growth but also induce cancer cell death.